#SoMe for #IC: Optimal use of social media in interventional cardiology. Issue 1 (8th March 2021) - Goldsweig, Andrew M.; Galper, Benjamin Z.; Alraies, Chadi; Arnold, Suzanne V.; Daniels, Matthew; Capodanno, Davide; Tarantini, Giuseppe; Cohen, David J.; Aronow, Herbert D.
Abstract: Social media allows interventional cardiologists to disseminate and discuss research and clinical cases in real‐time, to demonstrate and learn innovative techniques, to build professional networks, and to reach out to patients and the general public. Social media provides a democratic platform for all participants to influence the conversation and demonstrate their expertise. This review addresses the use of social media for these purposes in interventional cardiology, as well as respect for patient privacy, how to get started on social media, the creation of high‐impact social media content, and the role of traditional journals in the age of social media. In the future, we hope that interventional cardiology fellowship programs will incorporate social media training into their curricula. In addition, professional societies may adapt to the rapid dissemination of data on social media by developing processes to update guidelines more rapidly and more frequently.